Culturalist and Discursive approach of CSR Practices in African Context : The Case of MNCs operating in Madagascar - (:unkn) unknown (My University, 2022)
This article studies CSR (Corporate Social Responsibility) practices in the African context through the culturalist perspective and Pasquero’s (2005) model, using discursive analysis. Data were collected from 2017 to 2020 through eight semi-structured interviews with the CSR managers of MNCs (MultiNational Corporations) as well as through 38 internal and 63 external documents. Our results highlight how the Malagasy cultural context shapes the conception of CSR as a social convention and a set of operational practices. Our data also reveal the mechanisms by which CSR practices are embedded in the Malagasy cultural milieu, for example in relation to the values of fihavanana and tolo-tanana. This paper also presents a processual analysis of the negotiations and interactions between discourse, culture, cognitive process and CSR practices at work in the specific cultural context of Madagascar, where philanthropic and solicitude seem to correspond to a priority expectation from the stakeholders. Eventually, we discuss our results in light of the two components of modern CSR (i.e., philanthropy and caring) and the two cultural pillars (i.e., individualism and democratic pluralism) of Pasquero (2005, 2013) identified in our data.
Keywords: African Research